Assessing Land Degradation and Restoration: Strategies for Sustainable Management - Nikunj Shree (International Journal of Land, 2024)
Land degradation, defined as the loss of land quality and productivity, is a major danger to global food security, biodiversity, and water resources. This article investigates the numerous variables that contribute to land degradation, including deforestation, soil erosion, and land pollution. It emphasizes the urgent need for restoration efforts that focus on rehabilitating degraded lands through practices such as reforestation and agroforestry. Furthermore, the incorporation of climate-smart agriculture techniques is emphasized as a means of increasing resistance to climate change while also encouraging sustainable land management. Effective land management policies that balance development needs with ecological preservation are essential in addressing land degradation. Finally, community involvement is recognized as a crucial element for the success of restoration initiatives, where indigenous knowledge plays a vital role in ensuring culturally appropriate and ecologically sound projects. . This article promotes a comprehensive strategy to land restoration that prioritizes sustainability, resilience, and community engagement.
Keywords: Agroforestry; Biodiversity; Land degradation; climate-smart agriculture; community involvement; deforestation; ecological restoration; land restoration; soil erosion; sustainable land management